(untitled) (Research, Society and Development, 2021)
This study aimed to analyze the trends of Brazilian productions, based on theses and dissertations, about Permanent Health Education with Primary Care workers. It is a narrative review, developed with theses and dissertations available in the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel. The search was carried out in December 2020, with the strategy: “permanent health education” and “workers”. After applying the selection criteria, 24 productions made up the corpus of this study. Most studies come from dissertations (87.5%), with a qualitative design (66.6%), produced in institutions in the Southeast Region of Brazil (45%). Studies that investigated, mainly, the concept of Permanent Education in Health were evidenced, emphasizing that there is little clarity in the differentiation with the concepts of continuing education and education in service, which can interfere in its operationalization and in the results with the workers , managers and users. Also, it was identified that Permanent Education is a powerful strategy for the transformation of health practices. It was concluded that Permanent Education was shown as an opportunity for reflection on the health work process, in which the subjects have the possibility to express themselves, look at their own practice and seek new knowledge.